Mechanism of telomere maintenance: HP1α mediates liquid-liquid phase separation of telomeric nucleosome array - Putri, Dhira Anindya (Nanyang Technological University, 2023)
Heterochromatin protein 1 (HP1) is a highly conserved protein playing a critical role in the organisation and maintenance of the heterochromatic state. Dysregulation of HP1 have been shown to have downstream implications on ageing and cancer. Understanding the interaction between HP1α, a paralog of HP1, and telomeric DNA can provide valuable insights on how the integrity and stability of the genome is maintained in the nucleus. In this study, the interaction between HP1α and telomeric DNA in physiological conditions was investigated. Full-length telomeric DNA of 10x 157 bp telomeric repeats (T10) was obtained and reconstituted with histone octamer in vitro to form T10 nucleosome array. HP1α was obtained from E. coli cells and added to the reconstituted samples for an electrophoretic mobility shift assay (EMSA) binding assay and liquid-liquid phase separation study (LLPS) with confocal fluorescence microscopy. This study demonstrates that HP1α play a role in the organisation and regulation of telomeric chromatin structure by inducing the formation of phase separated droplets. These findings will pave the way for further understanding of the role that HP1α plays in the mediation of telomeric DNA structure and its downstream implications on ageing and cancer.